Networks, power and knowledge in the planning system: A case study of energy from waste. (April 2017) - Hacking, Nick; Flynn, Andrew
Highlights: A thick description of a sophisticated contestation of waste incineration technology. A longitudinal case study approach enables analysis of pre- and post-siting debate. Evidence of space and place mediating asymmetric power relations in communities. Evidence for bottom-up versus top-down political tension in governmentality approach. First use of knowledge construction diagrams with social network analysis. Abstract: Understanding the nature of power relations has been integral to debates in planning theory and planning practice since the 1960s. Current theoretical approaches to planning and power have evolved to a state of pluralism which impacts upon how planning is conceived of and practiced. We seek to examine power relations and knowledge via a multidisciplinary case study of an energy-from-waste (EfW) development based in South Wales. Centred on a highly contested technology, incineration, this case study incorporates in-depth, longitudinal interview data with social network analysis to build up a picture of competing framings of environmental health risk. In local environmental debates, planners are expected to be able to help resolve competition between conflicting interests and yet, in reality, such conflicts often appear intractable and have long been dubbed wicked problems. This is especially the case for waste management. In our in-depth case study, significant pre-existing power relations existed between the local planning authority (LPA), which was also the lead co-developer in the EfW project, and the local community. In terms of methods, we have been keen to unearth data that allows us to explore the nature of institutional and networked power as it plays out within a community over time. It is our contention that too often the dynamics of power have been underplayed because it is studied as a snapshot rather than over time. Here we have utilised a variety of methods – from key person interviews to social network analysis – to examine the application for development, the operation of the EfW and the closure of the plant – over a ten year time frame. By drawing upon a rich database we can better understand the ways in which, in the case of particularly contentious developments, power relations greatly hampered efforts at public participation. Our nuanced methodological approach reveals empirical evidence for tensions in theoretical approaches to power relations in the planning arena and we can identify how debates can move forward based on a more geographically informed perspective.